Preparation of super-toughened Poly(L-lactide) composites under elongational flow: A strategy for balancing stiffness and ductility. (26th May 2021) - Yang, Zhi-Tao; Yang, Ju-Xin; Fan, Jin-Hua; Feng, Yan-Hong; Huang, Zhao-Xia
Abstract: In this work, elongational flow supplied by a novel extrusion device, eccentric rotor extruder (ERE), was employed to prepare high-performance poly(L-lactide) (PLA)/poly(ε-caprolactone) (PCL) composites. Scanning electron microscopy (SEM) evidenced the elongational flow induced in-situ fiberization, in which the dispersed PCL were stretched into nanofibrils, consequently improved the interfacial adhesion of PLA/PCL. Differential scanning calorimetry (DSC), two-dimensional small-angle X-ray scattering (2D-SAXS), two-dimensional wide-angle X-ray diffraction (2D-WAXD) and dynamic mechanical analysis (DMA) were used to investigate the compatibility and crystallization of all composites. Consequently, we confirmed the enhanced compatibility and crystallinity were due to PLA's heterogeneous crystal nucleation on the nano-fibrillated PCL phases and the orientation of the PLA in a particular direction, which were considered induced by the elongational flow. Ultimately, we showed that the elongation at break of PLA with a low loading (20 wt%) of PCL is significantly improved to 476.7%, which is over 57 times that of the neat PLA. Meanwhile, the slight reduction in tensile strength is less than 20%. Enhanced thermal stability was also monitored due to the improved compatibility of PLA-PCL and the increased crystallinity of PLA. Graphical abstract: Image 1